PENERAPAN MENULIS PUISI MENGGUNAKAN METODE OUTDOOR STUDY SISWA KELAS V DI SDN 2 PABEDILAN KALER - Amaliah, Putri Nurul; Faiz, Aiman; Yuningsih, Dewi (Universitas Negeri Semarang, 2021)
Teachers who generally still apply classical learning, namely teaching in the classroom. This factor also causes students to find it difficult to write poetry because they are bored and cannot develop imagination, ideas that exist in students. This study aims to determine the learning process of poetry ability and find out the results of poetry writing skills using the outdoor study method. This research method uses a qualitative case study approach (case study). The subjects in this study were class V students. The data collection instruments used in this study were observation and interviews. By learning to write poetry using the Outdoor study method, it can improve student learning outcomes. Starting from the first meeting of students who have reached the KKM as many as 6 or 30% of students and students who have not reached the KKM as many as 14 or 70%. At the second meeting there were 13 or 65% students who had reached the KKM and 7 or 35% of students who had not reached the KKM. At the third meeting there were 16 or 80% of students who had reached the KKM and 4 or 20% of students who had not reached the KKM. At the fourth meeting, 19 or 95% of students who have reached the KKM and 1 or 5% of students who have not reached the KKM. The fourth meeting is the last meeting because based on the results of the fourth meeting the level of completeness can be achieved optimally.